2019
DOI: 10.1371/journal.pone.0220270
|View full text |Cite
|
Sign up to set email alerts
|

Trace amine-associated receptor gene polymorphism increases drug craving in individuals with methamphetamine dependence

Abstract: Background Methamphetamine (MA) is a potent agonist at the trace amine-associated receptor 1 (TAAR1). This study evaluated a common variant (CV) in the human TAAR1 gene, synonymous single nucleotide polymorphism (SNP) V288V, to determine the involvement of TAAR1 in MA dependence. Methods Participants (n = 106) with active MA dependence (MA-ACT), in remission from MA dependence (MA-REM), with active polysubstance dependence, in remission from polysubstance dependence, and with no history of substance dependence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…However, HT7 and PC4 were more frequently chosen for treatment of sleep disorder and sedation. [24][25][26][27] EEG study and fMRI study have suggested the pharmacophysiology of TEAS. [28,29] Our recent study found that the sedative effect of TEAS may be due to inhibition of ascending reticular activating system.…”
Section: Discussionmentioning
confidence: 99%
“…However, HT7 and PC4 were more frequently chosen for treatment of sleep disorder and sedation. [24][25][26][27] EEG study and fMRI study have suggested the pharmacophysiology of TEAS. [28,29] Our recent study found that the sedative effect of TEAS may be due to inhibition of ascending reticular activating system.…”
Section: Discussionmentioning
confidence: 99%
“…Non-functional mutations in mouse TAAR1 affect METH intake, hypothermia and conditioned taste aversion (82,83). Humans possess many TAAR1 variants with sensitivity to ligands (84)(85)(86)(87). However, the effects of TAAR1 variants on signaling cascades and risk for MUD, HAND, and neuropsychological disease will need to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the TAAR1 gene produce functional, sub-functional and non-functional variants 104 , although the sub-functional or non-functional variants are rare. Recently, Loftis et al 105 found that a synonymous single nucleotide polymorphism (SNP) in the human TAAR1 gene was associated with increased craving in methamphetamine users. Roles for non-functional TAAR1 genotypes have been proposed in obesity 106 , schizophrenia 107 and ‘mental illness’ 108 .…”
Section: Trace Amine Associated Receptor 1 (Taar1) and New Treatment ...mentioning
confidence: 99%
“…Therefore, the effects of TAAR1 agonists on addictive behavior associated with both stimulant classes is hypothesized to derive from reduced striatal dopamine release. Emphasizing the importance of TAAR1 in methamphetamine addiction, a recent paper found increased craving for methamphetamine in a subset of humans with a common TAAR1 genotype 105 .…”
Section: Taar1 and Implications For Treatmentmentioning
confidence: 99%